2008
DOI: 10.1007/s11956-008-1009-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of RNA-containing bacteriophages with host cell: MS2-induced mutants of E. coli and the occurrence of DNA-containing derivatives of the bacteriophage MS2

Abstract: Sensitive cells of Escherichia coli AB 259 Hfr 3000 infected with RNA-containing phage MS2 produce phage particles and simultaneously continue to divide, thereby segregating sensitive cells capable of sustaining new cycles of infection. Multiplication of phage in sensitive cells gives rise to phage-resistant forms in the progeny of these cells. It is shown that this phenomenon is due not to selection of pre-existing phage-resistant mutants, but is instead the result of interaction between the phage and the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Currently, the potential use of phage therapy in agriculture, veterinary biocontrol, food safety and in clinical treatment of human infections is also being studied [18,19,20,21,22,23,24,25,26]. A few studies have demonstrated that phages can be used to successfully prevent or control E. coli , even antibiotic resistant strains [27,28,29] and, to the best of our knowledge, only one study (from our group) have been done using the combination of phages and antibiotics to prevent the emergence of phage-resistant E. coli mutants [30].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the potential use of phage therapy in agriculture, veterinary biocontrol, food safety and in clinical treatment of human infections is also being studied [18,19,20,21,22,23,24,25,26]. A few studies have demonstrated that phages can be used to successfully prevent or control E. coli , even antibiotic resistant strains [27,28,29] and, to the best of our knowledge, only one study (from our group) have been done using the combination of phages and antibiotics to prevent the emergence of phage-resistant E. coli mutants [30].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that MS2 phage uptake into E. coli cells is mediated through binding to the F pilin protein in the F pili. [ 19 ] Only F+ (but not F-) E. coli cells can take up MS2 bacteriophage, resulting in lysis. Indeed, F- E. coli cells were used in our studies as a negative control.…”
Section: Discussionmentioning
confidence: 99%
“…F+plasmids can be easily transferred from E. coli cell to E. coli cell by conjugation. [ 19 ] It is also likely that a similar exchange is possible between different bacterial species. It is therefore surprising that there are no other reports of MS2 plaque formation in other bacterial species.…”
Section: Discussionmentioning
confidence: 99%